A Colony of Opportunity: African Economic Intermediaries, Rubber, and Capitalism in German Colonial Cameroon, 1884-1914 - Tristan Oestermann (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2025)
Taking German Cameroon as an example, this article uses the concept of the colonial intermediary to analyze Africans' role in colonial capitalism. While researchers have shown that the colonial state depended on Africans, the importance of African intermediaries in European trade has hardly been explored: European companies also depended on Africans for their business. The article argues that colonial capitalism in Cameroon was not only coercive but also opened new avenues for profit, social advancement, and accumulation for African traders, employees, and subcontractors. Studying the life histories of four African economic intermediaries, the article analyzes the opportunities of colonial capitalism, Africans' strategies of profit making, and Africans' role in colonial exploitation.
Keywords: N57; N77; N87; N97; 330; intermediaries; colonialism; business; trade; Cameroon; rubber; capitalism; German colonialism